Enhancing Young Learners' English Vocabulary Through Songs and Interactive Games - Meisuri, Wiwiek; Kemit, Lateresiana; Arafat, Kirana Rizki; Rambe, Miftahul Jannah; Kurniawan, Wahyu (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2025)
This study explores the effectiveness of interactive teaching methods in enhancing English vocabulary acquisition among first-grade students at Madrasah Ibtidaiyah Madrasatul Ikbar, where the authors taught 17 students aged 6–8 years. The background of this research is based on the initial observation that students had very limited English vocabulary and struggled with pronunciation, as noted by the school head during interviews. The purpose of this study is to improve students' vocabulary comprehension and pronunciation through engaging and structured learning activities. The research is grounded in the theory of active learning, which emphasizes student engagement through repetition, songs, and interactive exercises. Using a qualitative approach and observational methods, the authors conducted five teaching sessions covering vocabulary topics such as animals, fruits, numbers, and classroom objects. Each session incorporated songs, games, and printed exercises to reinforce learning. The results indicate significant progress in students’ vocabulary recall and pronunciation, with notable improvements observed in their confidence and participation. The study concludes that interactive and repetitive teaching strategies effectively enhance English learning in young children, fostering both engagement and comprehension.